DIRECTIONS FOR IMPROVING THE SYSTEM OF PROVIDING ADMINISTRATIVE SERVICES IN PUBLIC AUTHORITIES IN UKRAINE - Кравченко, Олена (SWorldJournal, 2023)
The article justifies the relevance of researching the directions for improving the system of providing administrative services in public authorities in Ukraine, which is linked to the country’s European integration course. The aim of the article is to id